The inhibition of biodegradation on building limestone by plasma etching - Ding, Yufan (2022)
Plasma etching is an innovative technique that has been recently applied in the cleaning of soiled archaeological objects. This research investigated the use of low-pressure plasma etching in cleaning microbial contaminations on an oolitic limestone from an UNESCO World Heritage listed monument: the Batalha Monastery in Central Portugal. The cleaning effect was assessed by FTIR, SEM, optical microscope, and cell viability index measurement. Experimental work suggests that plasma discharge can cause rupture in the microbial cell structures and is helpful in removing microorganisms from the surface of the stone. At the macroscopic level, detachment of microbial crust was also observed in plasma etched bio-deteriorated limestone surfaces. Furthermore, plasma etching can inhibit the microbial growth by decomposing and eliminating the sugar-containing compounds on the limestones, thus eliminating a major nutrient supply for microbial metabolism and reproduction. Plasma etching can therefore be regarded as a fast and eco-friendly conservation tool for stone heritage architecture to prevent/reduce the onset of bio-colonization and biodegradation.